Hybridization of inorganic CoB noncrystal with graphene and its Kubas-enhanced hydrogen adsorption at room temperature. Issue 96 (29th September 2016) - Li, Xiaobo; Sun, Shuchao; Zhang, Jianjiao; Luo, Kan; Gao, Peng; Wu, Tingting; Du, Shiyu; Wang, Ying; Zhou, Xiaoming; Sha, Linna; Yang, Yurong; Yang, Piaoping; et al.
Abstract : In this work an archetypical hybrid material has been prepared by the reaction of an inorganic CoB noncrystal with graphene by a high-energy ball-milling process, which showed an enhanced electrochemical hydrogen storage ability induced by the Co–B–C structure. Abstract : Hybridization of inorganic compounds with graphene-based materials can give rise to various enhanced properties, in which constructing a chemical bond stabilized hybrid structure is of primary importance. In this work, an archetypical hybrid material has been prepared by the reaction of an inorganic CoB noncrystal with graphene at room temperature with a high-energy ball-milling process. Experimental characterization results prove that the inorganic CoB noncrystal is stably pinned to graphene through B–C chemical bonds. The hybrid material shows a high electrochemical hydrogen storage capacity at room temperature. Based on the detailed experimental measurements and theory calculations, the enhanced electrochemical hydrogen storage ability is identified as a Kubas-enhanced hydrogen adsorption mechanism induced by the Co–B–C structure.